The Obsession of Women Characters in Daphne du Maurier's 'Rebecca' - Legiana, Suci; Hetami, Fatma (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
The objectives of this study are to analyze how is the obsession of the women characters and to explain how the obsession of the women characters influences their behavior described in Daphne du Maurier’s Rebecca. The object of the study is a novel entitled Rebecca, written by Daphne du Maurier. This study is a descriptive qualitative study by applying Freudian psychoanalytic theory. The data of the study were collected by reading, identifying, inventorying, classifying, selecting, and reporting. By using Freudian psychoanalytic theory, the analysis focused on the women's character's obsession. The results show (1) Rebecca’s obsession in gaining power through fake appearances to get wealth and honor. Then, Mrs de Winter obsession in getting her husband’s love influenced by her father’s figure so that she has an electra complex. Further, Danvers obsession in loving Rebecca makes her have selfishness. (2) The influence of Rebecca’s obsession makes her have a narcissistic personality disorder. Then, the influence of Mrs de Winter obsession makes her envy, and finally she imitates Rebecca to increase her confidence in getting her husband’s love. Further, the influence of Danvers obsession makes her a Rebecca worshiper. Keywords: Characters, Obsession, Psychoanalytic, Rebecca, Women